Anticodon-edited tRNA enables translational readthrough of COL4A5 premature termination codons - Kohei Omachi; Joseph J. Porter; John D. Lueck; Jeffrey H. Miner (PLoS ONE, 2025)
Alport syndrome is caused by variants in COL4A3 , COL4A4 , or COL4A5 , which encode the α3α4α5 chains of type IV collagen. These variants result in defects in the glomerular basement membrane (GBM) and impaired kidney function. Nonsense variants result in truncated proteins lacking the NC1 domain, thereby preventing proper GBM assembly and function and causing the most severe forms of the disease. Restoring full-length protein expression represents a potential therapeutic strategy for Alport syndrome and related disorders. Anticodon-edited transfer RNAs (ACE-tRNAs), which promote premature termination codon (PTC) readthrough, have shown promise in diseases such as cystic fibrosis, but their application in Alport syndrome remains unexplored. To assess the potential of ACE-tRNAs for PTC readthrough of COL4A5 nonsense variants, we employed a C-terminal NanoLuc-fused COL4A5 reporter system in which luminescence is produced only upon full-length protein translation. We introduced ACE-tRNAs into HeLa and 293T cells expressing one of four COL4A5 nonsense variants ( S36X, R1563X, S1632X, and R1683X ) identified in patients with X-linked Alport syndrome. Readthrough efficiency was evaluated via NanoLuc luminescence and western blotting. Furthermore, we assessed the efficiency of ACE-tRNA-restored α3α4α5 heterotrimer formation using a split NanoLuc-based assay. Our results show that application of ACE-tRNAs led to restored C-terminal luminescence across all four COL4A5 nonsense variants, indicating successful readthrough and full-length translation. Moreover, the restored COL4A5 proteins formed α3α4α5 heterotrimers. These findings support ACE-tRNA-mediated nonsense suppression as a promising therapeutic strategy for Alport syndrome, with the potential to restore GBM integrity in patients harboring nonsense variants.